Association of self‐rated health with type and frequency of social interaction during the declaration of COVID‐19 state of emergency among Japanese community‐dwelling oldest‐old adults. Issue 5 (22nd March 2022) - Akaida, Shoma; Nakai, Yuki; Shiratsuchi, Daijo; Tomioka, Kazutoshi; Taniguchi, Yoshiaki; Sato, Nana; Wada, Ayumi; Kiuchi, Yuto; Shono, Saki; Shiiba, Ryuhei; Tateishi, Mana; Makizako, Hyuma
Abstract : Aim: To investigate whether the type and frequency of social interaction during the state of emergency due to coronavirus disease were associated with self‐rated health (SRH) after the state of emergency. Methods: Data from a cross‐sectional study were collected for 889 oldest‐old adults in Bibai City, Hokkaido, Japan. In total, 612 participants (mean age: 83.0 ± 4.3 years; women: 51.8%) were included in the analysis, taking biological sex into account. The self‐reported questionnaire included questions about demographic variables, SRH (July 2020, after the emergency), and the type and frequency of social interaction (March 2020, during the state of emergency). Results: There was no significant association between social interaction and SRH in men ( P  > 0.05). Women who had social interactions (both face‐to‐face and non‐face‐to‐face) more than once a week during the state of emergency reported higher SRH after the emergency than those who did not (odds ratio 2.17, 95% confidence interval 1.07–4.41). Conclusions: Having both types of interaction more than once a week during the state of emergency was related to higher SRH after the emergency among oldest‐old women. It is suggested that having opportunities for both types of interaction at least once a week would potentially be beneficial for high SRH in women, even in situations where the declaration of a state of emergency restricts face‐to‐face interaction. Geriatr Gerontol Int 2022; 22: 405–411 .